2018
DOI: 10.1037/neu0000486
|View full text |Cite
|
Sign up to set email alerts
|

The life span distribution of autobiographical memory in Alzheimer’s disease.

Abstract: Older adults diagnosed with AD demonstrate increased recollection of personal semantic and episodic events from the remote past relative to the recent one. The findings are discussed in relation to prominent models of memory consolidation. (PsycINFO Database Record (c) 2018 APA, all rights reserved).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…Moreover, it has been suggested that the degree of impairment of semantic ABM may depend on the stage of the disease. While episodic autobiographical memory can be affected in early AD, semantic components may be preserved, becoming impaired only in more severe stages of the condition (Seidl et al, 2011;Kirk and Berntsen, 2018). The temporal gradient is also evident from the early stages of dementia for episodic ABM, while semantic ABM seems to be characterized by a flatter distribution across lifetime periods (Seidl et al, 2011).…”
Section: The Remote Self In Admentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, it has been suggested that the degree of impairment of semantic ABM may depend on the stage of the disease. While episodic autobiographical memory can be affected in early AD, semantic components may be preserved, becoming impaired only in more severe stages of the condition (Seidl et al, 2011;Kirk and Berntsen, 2018). The temporal gradient is also evident from the early stages of dementia for episodic ABM, while semantic ABM seems to be characterized by a flatter distribution across lifetime periods (Seidl et al, 2011).…”
Section: The Remote Self In Admentioning
confidence: 98%
“…Specifically, retrieval of remote material seems to be better preserved than recent memories. Overall, it has been highlighted that in AD ABM impairments are characterized by a temporal gradient for both episodic and semantic components (Leyhe et al, 2009;Thomann et al, 2012;De Simone et al, 2016;Kirk and Berntsen, 2018).…”
Section: The Remote Self In Admentioning
confidence: 99%
“…Barnabe et al . () and more recently Kirk and Berntsen () highlighted that the presence/absence of TG in different studies may be due to the different number of retrieved epochs and events assessed by the two tests. In particular, the AMI requires three events to be retrieved from three different periods of life (childhood, early adult life, and recent adult life; conversely, the AI requires that a single event be recalled from five periods of life (early childhood, adolescence–teenage years, early adulthood, middle age, and the previous year).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported a significant TG for personal episodic (but not for semantic) memories in patients with preclinical AD (a condition known as Mild Cognitive Impairment [MCI]; Greene et al ., ; Leyhe et al ., ) and fully developed AD (Greene et al ., ; Irish, Lawlor, et al ., ). Moreover, TG for semantic information in patients with AD has been documented either in isolation (Gilboa et al ., ; Irish et al ., ; Ivanoiu et al ., ) or in association with TG for personal episodic memories (Kirk & Berntsen, ; Kopelman, ; Leyhe et al ., ). Finally, autobiographical episodic memory deficits have also been documented in the absence of any gradient (Irish, Hornberger, et al ., ; Murphy et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation